Landasan Konseptual Kurikulum Pendidikan: Perspektif Kedudukan, Jenis, dan Konsep Ideal - Achmad Junaedi Sitika; Aliyah Salsabila Putri; Siti Lathifah; Tiara Khaerani Hasibuan (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze and identify the position, types, and ideal concept of curriculum within the educational system, particularly in the context of Indonesia's national education. The curriculum is regarded as the core of the educational system as it serves as the foundation for lesson planning, educational goal setting, material selection, and ensuring equitable access to quality education. The role of the curriculum in education carries strategic functions, including serving as a guide for teachers, a reference for evaluating the learning process, and a framework for developing students' holistic and sustainable competencies. The types of curriculumare classified based on orientation (traditional to modern), value systems (from humanistic to reconstructionist), and modes of implementation (theoretical or practical). This study employs a qualitative approach through literature review, drawing on educational books, peer-reviewed journal articles, and government policy documents. In the Indonesian context, the evolution of the curriculum from 1947 to 2023 reflects socio-political dynamics and shifts in global educational paradigms. The latest curriculum reform, known as Kurikulum Merdeka, represents an effort toward modernization and responsiveness to contemporary needs, emphasizing differentiated learning, character building, and flexibility in developing students' potential. The ideal curriculum concept proposed in this study is one that integrates academic, humanistic, technological, and social reconstruction approaches to create relevant, participatory, and meaningful learning experiences for students in addressing the challenges of the 21st century.